CITRA PEREMPUAN DIFABEL DI MEDIA: SEBUAH ANALISIS WACANA KRITIS - Aini, Hanifah Risti (Universitas Muhammadiyah Metro, 2020)
This research trying to see diffable’s imagery in the media –including quality of discrimination. Because of some media are less friendly to the diffable and also perpetuate discrimination against this group. Whereas the media as a construct of social reality viewed as a quite effective way to correcting the perceptions about diffable. The objects of this research are articles found in Tempo.co and Kebumen Ekspres. The method used in this research is media text analysis of Sara Mills discourse analysis. The results showed that diffable imagery in Tempo.co is no longer viewed as an object of inspiration or porn inspiration, object of charity, object of verbal abuse but as a person in general. In the other hand, Kebumen Ekspres describes diffable as object of inspiration, objects of charity, objects of verbal abuse and lead the reader to the ideology of normality. Kebumen Ekspres considers that diffable achievement is a thing that quite prestige for the diffable so it is displayed excessively.